Early Jewish Parables and Fables as Non-Religious Narratives - THURÉN, Lauri (Studia Universitatis Babeș-Bolyai Sacra Scripta, 2026)
To understand the parables of Jesus, it is interesting to compare them with other early Jewish persuasive narratives, including parables but also fables. Recognizing their common features and functions yields a more reliable interpretation of each genre and individual story. To this end, I will scrutinize some examples of these narratives with modern argumentation analysis. I will argue that, in their original context, these stories function best as non-religious persuasive narratives. Each of them aims at enhancing the audience’s acceptance of some general principle, which can then be applied to religious discussion. Within these stories, however, nothing requires an allegorical and directly religious interpretation. On the contrary, such axiomatic readings obscure their message and function.